Dynamics of alternative polyadenylation in single root cells of Arabidopsis thaliana - Bi, Xingyu; Zhu, Sheng; Liu, Fei; Wu, Xiaohui (Frontiers in Plant Science, 2024)
Single-cell RNA-seq (scRNA-seq) technologies have been widely used to reveal the diversity and complexity of cells, and pioneering studies on scRNA-seq in plants began to emerge since 2019. However, existing studies on plants utilized scRNA-seq focused only on the gene expression regulation, and there is still a lack of research with single-cell resolution on the transcript-isoform level. As an essential post-transcriptional mechanism for regulating gene expression, alternative polyadenylation (APA) generates diverse mRNA isoforms with distinct 3′ ends through the selective use of different polyadenylation sites in a gene. APA plays important roles in regulating multiple developmental processes in plants, such as flowering time and stress response. In this study, we comprehensively compiled a single-cell APA atlas from five scRNA-seq studies, covering over 150,000 cells spanning four major tissue branches, twelve cell types, and three developmental stages. High-confidence poly(A) sites in single root cells were identified and quantified. Moreover, three kinds of APA markers were identified for exploring APA dynamics in single cells, including differentially expressed poly(A) sites based on APA site expression, APA markers based on APA usages, and APA switching genes based on 3′ UTR (untranslated region) length change. By integrating both the APA information and the gene expression profile, cell type annotations of single root cells were refined. This study reveals that APA provides an additional layer of information for determining cell identity and provides a landscape of APA dynamics during Arabidopsis root development.